Feasibility of pre-treating wastewater/water to prevent/minimize reverse osmosis (RO) membrane biofouling using H2O2 - Sim, Hui Xian (2017)
Hydrogen peroxide (H2O2) is widely used in water and wastewater treatment as a powerful oxidant for contamination degradation. H2O2 could potentially serve as an anti-biofouling agent in reverse osmosis systems. The dependence of the biocidal efﬁciency of H2O2 on cell density and H2O2 dosage by using a model bacterium Pseudomonas aeruginosa (PAO1) was studied. Disinfection rate constants k were found to be higher at higer dosages of H2O2 and this is due to higher frequency of collision. The effect of H2O2 to remove PAO1 was found to be of higher efficiency with longer reaction time, higher concentration of H2O2 and lower PAO1 cell density. The number of PAO1 living cells was found reduced after treatment with H2O2 over time, suggesting that H2O2 does have killing power on PAO1. However, H2O2 could not fully inactivate PAO1 even after 60 minutes. This was because the disinfection of PAO1 using H2O2 reached a reaction plateau stage 5 minutes after the start of experiment. Therefore, H2O2 is not an effective disinfection agent against PAO1. H2O2 disinfection efficiency of PAO1 was compared to that of Ozone in the aspects of cost. H2O2 was found to be less cost effective than Ozone. Due to time constraint, the pre-treatment of real wastewater sample with H2O2 and the running of sample with a reverse osmosis membrane were not carried out.